Chaotic masking for securing RFID systems against relay attacks. Issue 12 (27th June 2012) - Malek, Behzad; Miri, Ali
ABSTRACT The relay attack is a simple yet effective attack against most radio‐frequency identification (RFID) authentication systems. Because of the minimalist design of an RFID system, a lightweight authentication scheme must be designed to provide a strong level of security for low‐cost RFID tags. In this work, we propose a simple but secure masking scheme that counters the relay attack in RFID systems. Our scheme is the first solution based on the chaos suppression theory. We have exploited the chaotic characteristics of a dynamic Lorenz controller to distinguish a legitimate RFID reader from a proxy reader in the relay attack. We also show that the proposed approach is practical using simulation results. Copyright © 2012 John Wiley & Sons, Ltd.